Einstein Relation in Compound Semiconductors and Their Nanostructures - Ghatak, Kamakhya Prasad; Bhattacharya, Sitangshu; De, Debashis (Springer Series in Materials Science, 2009)
This is the first book solely devoted to the Einstein relation in compound semiconductors and their nanostructures. The materials considered are nonlinear optical, III-V, ternary, quaternary, II-VI, IV-VI, Bismuth, stressed compounds, quantum wells, quantum wires, nipi structures, carbon nanotubes, heavily doped semiconductors, inversion layers, superlattices of nonparabolic materials with graded interfaces under magnetic quantization, quantum wire superlattices with different band structures and other field assisted systems. The influence of light on the Einstein relation in semiconductors and their nanostructures has also been investigated in detail by formulating the respective dispersion relations which control the transport in such quantum effect devices. The book deals with many open research problems.